Identifying some regularities of the aerodynamics around wind turbines with a vertical axis of rotation - Tanasheva, Nazgul; Ranova, Gulden; Satybaldin, Amangeldy; Dyusembaeva, Ainura; Bakhtybekova, Asem; Shuyushbayeva, Nurgul; Kyzdarbekova, Sholpan; Sarzhanova, Indira; Abdirova, Nurgul (Eastern-European Journal of Enterprise Technologies, 2024)
The design of wind turbines with a vertical axis of rotation is quite simple, which successfully increases the level of efficiency. Existing vane wind turbines have a shortage of currents in the form of negative torque, and installations operating on the Magnus effect have a low lifting force. In this regard, the development and research of installations operating at speeds from 3 m/s, with combined blades with increased work efficiency is an urgent topic. The object of the study is a wind turbine consisting of a system of rotating cylinders and fixed blades operating at low air flow speeds starting from 3 m/s. Numerical studies were carried out using the Ansys Fluent program and the implemented k-ε turbulence model. A special feature of the work is the combined use of two lifting forces: a cylinder and fixed blades, which made it possible to increase the output aerodynamic parameters. Calculations were performed for incoming flow rates of 3 m/s, 9 m/s, 15 m/s and cylinder rotation speeds of 315 rpm, 550 rpm, 720 rpm. It is determined that the period of change of the moment of forces T is 0.5 m/s, which corresponds to 2 revolutions of the wind wheel per minute. It was found that the cylinder rotation frequency in the range from 315 rpm to 720 rpm does not affect the period of change in the moment of forces, but the amplitude of the moment of forces increases with decreasing rotation frequency. The dependences of the rotation speed of the wind wheel on the velocity of the incoming flow, found by the method of sliding grids and 6DOF, are also obtained. It is determined that the installation begins to make revolutions from 3 m/s, with a positive torque of forces. The field of practical application of the numerical results will be useful for further research of wind turbines with combined blades